Treatment of Obstructive sleep apnea- A Review - Ahmad, Fahad; Chopra, Anish (Journal of Orofacial Research, 2019)
Obstructive sleep apnea (OSA) is a serious disease with neurocognitive and cardiovascular sequelae. Various population-based studies show that 2% of women and 4% of men are affected with symptomatic OSA; however, the prevalence of asymptomatic OSA is quite high which affect 20%–30% of the middle-aged population. It can be diagnosed on the basis of characteristic history (snoring, daytime sleepiness) and physical examination (increased neck circumference); nevertheless, overnight polysomnography is the gold standard to confirm the presence of the disorder. Many treatment modalities have been evolved to address the disease, which includes lifestyle modification; medical therapy; CPAP; oral appliances; and surgical correction. Although the initial choice of treatment is CPAP in most of the patients, it can be tailored according to Apnea-hypopnea index (AHI) and the need of the individual patient. In addition, surgical interventions are the preferred option in certain cases which not only provide a quick cure of OSA but also correct many facial anomalies.